2015
DOI: 10.1016/j.kjms.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Burch–Schneider cage and structural allografts in complex acetabular deficiency: 3‐ to 10‐year follow up

Abstract: This study aimed to evaluate retrospectively the clinical outcomes and complications of structural allografts and Burch-Schneider antiprotrusio cages to treat severe acetabular defects in revision total hip arthroplasty (THA). Between July 2003 and December 2010, 29 patients (representing 31 hips) underwent revision THA using structural allografts and Burch-Schneider cages for acetabular reconstruction. The patients had a mean age of 59 years (range, 37-79 years). Seventeen hips had a Paprosky IIIA defect, 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 37 publications
2
43
0
2
Order By: Relevance
“…The outcome of this study corresponds with the findings in literature: sufficient support should be available for long-term stability of a Burch-Schneider cage [6,8,9,10]. These findings were based on the relatively high failure rates of cages in Paprosky IIIB defects compared to smaller defects.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The outcome of this study corresponds with the findings in literature: sufficient support should be available for long-term stability of a Burch-Schneider cage [6,8,9,10]. These findings were based on the relatively high failure rates of cages in Paprosky IIIB defects compared to smaller defects.…”
Section: Discussionsupporting
confidence: 86%
“…Selecting a suitable treatment option for each patient is essential in order to avoid implant failure in hip arthroplasty. Clinical studies have reported that support beneath a Burch-Schneider cage has a large effect on the implant survival rate [6,8,9,10]. This study investigated if the effect of Burch-Schneider cage support on the implant and bone stresses can be demonstrated by means of finite element analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In favourable conditions, viable bone tissue has been demonstrated to grow on titanium surfaces thus eventually providing a durable support for the cage. [1][2][3][4][5][6] Modern trabecular metal systems provide versatility trough modular options with better osteoconductivity in order to maintain a stable bone-prosthesis interface, however, these implants come with higher costs and they may not be available in some areas or health systems. Although the initial studies have been reported high success rates in acetabular reconstruction with tantalum cages and attributing their superior biologic fixation properties, subsequent long-term follow-up showed less favourable outcomes.…”
Section: Titanium Cage Reconstruction Of Acetabular Defects In Revisimentioning
confidence: 99%